2021
DOI: 10.15407/ufm.22.03.307
|View full text |Cite
|
Sign up to set email alerts
|

TiMn2-Based Intermetallic Alloys for Hydrogen Accumulation: Problems and Prospects

Abstract: the main advantages of hydrogen as an energy carrier in comparison with currently used hydrocarbons are determined. By comparing the advantages and disadvantages of available methods of hydrogen storage, it was proved that storage of it in a bound state (hydrides) provides the largest amount of stored hydrogen per unit weight of the container and is the safest method. As shown, the alloys based on AB 2type intermetallics are the most promising materials for safe storage and transportation of hydrogen in the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 145 publications
2
8
0
Order By: Relevance
“…As seen from Figure 4, the process of hydrogen absorption for all alloys at elevated temperatures has a similar nature and consists of two stages with noticeably different rates of interaction. The data of [4,10] allow to suggest that the first stage of interaction with hydrogen corresponds to the formation of a supersaturated solid solution, whereas the second is the formation of the hydride phase.…”
Section: The Process Of Hydrogen Sorption-desorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen from Figure 4, the process of hydrogen absorption for all alloys at elevated temperatures has a similar nature and consists of two stages with noticeably different rates of interaction. The data of [4,10] allow to suggest that the first stage of interaction with hydrogen corresponds to the formation of a supersaturated solid solution, whereas the second is the formation of the hydride phase.…”
Section: The Process Of Hydrogen Sorption-desorptionmentioning
confidence: 99%
“…It has now been shown that storing hydrogen in a bound state (metal hydrides) is a more cost-effective and safe way than in liquid or gaseous states [1][2][3][4][5]. Among the existing variety of materials for hydrogen sorption, the AB 2 -type intermetallics (hexagonal Laves phase of C14 type) and multiphase alloys based on them are recently used, especially in transport [6][7][8][9][10]. In this class of materials, an important place is occupied by the Ti-based alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influence on the phase composition and physical and mechanical characteristics of metallic materials through their interaction with hydrogen is the basis of many technologies. In particular, the temporary saturation of metals and alloys with hydrogen provides an effect on the defects of their crystal structure, phase composition and microstructure (so-called hydrogen treatment) [1,2], which is used to achieve the desired mechanical properties. Metal hydrides are brittle and rather low-strength materials compared to the source materials [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above, modern developments in the field of hydrogen energy are important, which require detailed knowledge of the kinetics of the processes of inverse saturation of materials with hydrogen for the development of hydrogen batteries [2,[23][24][25]. That is why the conditions of interaction of various metals and alloys with hydrogen, including thermal, pressure and time parameters of hydrogen saturation and the reverse process of hydrogen evolution from metals, are extremely important data for basic knowledge and applied developments.…”
Section: Introductionmentioning
confidence: 99%